Making war at Fort Hood [ life and uncertainty in a military community - MacLeish, Kenneth T. , 1979- (Princeton University Press, 2013)
Making War at Fort Hood offers an illuminating look at war through the daily lives of the people whose job it is to produce it. Kenneth MacLeish conducted a year of intensive fieldwork among soldiers and their families at and around the US Army's Fort Hood in central Texas. He shows how war's reach extends far beyond the battlefield into military communities where violence is as routine, boring, and normal as it is shocking and traumatic. Fort Hood is one of the largest military installations in the world, and many of the 55,000 personnel based there have served multiple tours